Peluang Bisnis Bagi Umkm Di Era Digital (Studi Kasus Pada Umkm Sheo Sweet Di Kecamatan Ngunut, Kabupaten Tulungagung) - Nur Miftitah, Firda Aulia; Mashudi Mashudi (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
The rapid development of technology makes people experience lifestyle transformation, especially in carrying out daily activities such as consumption patterns, schools, and so on. But not only that, but the development of this technology has also changed MSMEs (micro, small and medium enterprises) which were originally traditional to turn into the digital era. Economic aspects based on the use and empowerment of information technology and digital communications. In Indonesia, the digital economy is currently developing quite rapidly and in tandem with the growing market power available. This article aims to describe business opportunities for MSMEs in the digital era where the case study is Sheo Sweet's MSMEs in Ngunut District, Tulungagung Regency. The research method used is qualitative with a case study approach. Data collection techniques through observation and in-depth interviews. The research results obtained show that business opportunities for MSMEs in the digital era are quite diverse, namely: promotion through marketplaces is much easier, more efficient and reduces costs, renewal of marketing methods that used to be traditional to modern ones to keep up with the times, access to markets is easier and wider, strengthen branding and be able to innovate products to make them more varied. Keywords: Business Opportunities, MSMEs, Digital Era